Organic light-emitting material containing phosphine oxide group and application of organic light-emitting material in organic light-emitting device

By introducing phosphineoxy groups into TADF materials, utilizing its unique spatial configuration and triplet energy characteristics, the challenges of TADF materials in high color purity and stability are solved, achieving high efficiency and long-life organic electrogenesis Light emitting device.

CN119192247APending Publication Date: 2024-12-27CHENGDU VITUOLI FLEXIBLE ELECTRONICS TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411323608.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

TADF materials face challenges in achieving blue light emission with high color purity, and are prone to roll-off at high brightness, and are insufficient instability, which affects its commercial application.

Method used

The organic luminescent material with phosphine-containing phosphine-oxy groups is used. Its unique spatial configuration inhibits the molecular stacking effect, maintains the material morphology stable, and improves the device efficiency and life through the full utilization of triplet energy.

Benefits of technology

It significantly improves the color purity and efficiency of the device, suppresses the efficiency roll-off phenomenon, extends the operating life of the device, and improves the chemical and device stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192247A_ABST
    Figure CN119192247A_ABST
Patent Text Reader

Abstract

The invention discloses an organic light-emitting material containing a phosphinoxyl group and an application of the organic light-emitting material in an organic light-emitting device, and relates to the technical field of OLED (Organic Light Emitting Diode), and the organic light-emitting material comprises a compound taking phosphinoxyl group acridone as a main body skeleton. The OLED device provided by the invention is high in efficiency, relatively small in efficiency roll-off degree, low in starting voltage, capable of keeping relatively high device efficiency under high brightness, and good in film forming characteristic. Compound structure as follows: # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of organic electroluminescent devices, in particular to a luminescent material and its application in organic electroluminescent devices. Background Art

[0002] With the improvement of people's viewing needs and visual enjoyment, the existing display technology cannot meet people's increasingly high requirements for display devices. Finding new high-efficiency and lower-cost display devices has become people's pursuit. Organic electroluminescent diodes have excellent performance in display, such as low power consumption, easy bending, fast response speed, wide viewing angle, large-area display and full range of luminous colors, as well as their broad application prospects in solid-state lighting, making OLEDs widely concerned by academia and industry.

[0003] As a new type of organic light-emitting diode (OLED) material, TADF material has many potential advantages, but there are also some challenges and problems. TADF material still faces challenges in achieving high color purity blue light emission; when TADF material works at high brightness, efficiency roll-off may occur, that is, as the brightness increases, the luminous efficiency of the device decreases; the stability of TADF material is another key issue. Including the chemical stability of the material itself and the stability during the operation of the device. Improving the stability of TADF material and extending its working life are crucial to achieving commercial applications.

[0004] Due to the nature of the phosphorus atom itself, it can form 5 covalent bonds, so the phosphine oxygen functional group is very easy to connect with other groups to form a derivative with it as the core. Since the oxygen atom has a strong electronegativity, this makes the phosphine oxygen structure highly polarized and has a strong electron-withdrawing property. The triphenylphosphine oxygen unit formed by the electron-withdrawing phosphine oxygen group connecting the benzene ring also has a strong electron-withdrawing property, which will also have a significant impact on the energy level structure of the formed compound. Due to the influence of the conjugation effect, the core of many molecules will reduce the triplet energy level when the molecular chain length is extended, while the triphenylphosphine oxygen group with a spatial tetrahedral structure will not extend the conjugation, thereby ensuring that the triplet energy level is not reduced. Because the unique spatial configuration of triphenylphosphine oxygen derivatives suppresses the molecular stacking effect, this is conducive to maintaining the morphological stability of the material. Summary of the invention

[0005] The first object of the present invention is to provide an organic light-emitting material containing phosphine oxide, which has good photoelectric properties and low efficiency roll-off characteristics.

[0006] An organic light-emitting material containing a phosphine oxygen group, having a compound having a structure shown in Formula 1:

[0007]

[0008] wherein R1, R2, R3 and R4 are independently hydrogen, deuterium, halogen, substituted or unsubstituted alkyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 ring atoms, substituted or unsubstituted heteroalkyl having 1 to 20 carbon atoms, substituted or unsubstituted heterocyclyl having 3 to 20 ring atoms, substituted or unsubstituted aralkyl having 7 to 30 carbon atoms, substituted or unsubstituted alkoxy having 1 to 20 carbon atoms, substituted or unsubstituted aryloxy having 6 to 30 carbon atoms, substituted or unsubstituted alkenyl having 2 to 20 carbon atoms , substituted or unsubstituted aryl having 6-30 carbon atoms, substituted or unsubstituted heteroaryl having 3-30 carbon atoms, substituted or unsubstituted silyl having 3-20 carbon atoms, substituted or unsubstituted arylsilyl having 6-20 carbon atoms, substituted or unsubstituted alkylgermanyl having 3-20 carbon atoms, substituted or unsubstituted arylgermanyl having 6-20 carbon atoms, substituted or unsubstituted amino having 0-30 carbon atoms, acyl, carbonyl, carboxylic acid, ester, cyano, isocyano, hydroxyl, thiol, sulfinyl, sulfonyl, phosphino, and combinations thereof.

[0009] Furthermore, the structure of the compound is as follows:

[0010]

[0011]

[0012]

[0013]

[0014]

[0015]

[0016] The second object of the present invention is to provide an application of an organic light-emitting material containing a phosphine oxygen group in an organic electroluminescent device, wherein the organic electroluminescent device comprises the above-mentioned light-emitting material.

[0017] Furthermore, the luminescent material is doped into the luminescent layer of the organic electroluminescent device.

[0018] The organic light-emitting material containing phosphine oxide provided by the present invention has the following advantages compared with the prior art:

[0019] Compared with traditional fluorescent materials, the phosphine-oxy group-containing organic light-emitting material of the present invention can fully utilize triplet energy, thereby greatly improving device efficiency. Compared with known TADF materials, the half-peak width of the spectrum is significantly reduced, and its color purity is significantly improved; the device efficiency roll-off phenomenon is significantly suppressed, and the device life is significantly improved. DETAILED DESCRIPTION

[0020] Example

[0021] The general synthetic formula of the compound of the present invention is as follows:

[0022]

[0023]

[0024]

[0025] Preparation of intermediate A (R2 = R4 = H): 2-bromoaniline (R2 = H, 1 equiv.), o-iodobromobenzene (R4 = H, 2 equiv.), tris(dibenzylideneacetone)dipalladium (0.05 equiv.) and sodium tert-butoxide (3 equiv.) are added into a reaction bottle in sequence, nitrogen is replaced three times, toluene is added, and reflux reaction is carried out under nitrogen for 24 hours. After the reaction is completed, the system is restored to room temperature, extracted and washed with dichloromethane and saturated brine, the organic phase is recovered and dried with anhydrous magnesium sulfate, the solvent is removed by distillation under reduced pressure, and then the crude product is separated and purified by column chromatography to obtain intermediate A;

[0026] Preparation of intermediate B (R2=R4=H): The prepared intermediate A (1 equiv.), di-tert-butyl dicarbonate (3 equiv.) and 4-dimethylaminopyridine (0.5 equiv.) were dissolved in tetrahydrofuran, and water was added after 12 hours to quench the reaction, and the mixture was extracted and washed with dichloromethane and saturated brine, and the organic phase was recovered and dried over anhydrous magnesium sulfate, and the solvent was removed by distillation under reduced pressure, and then the crude product was separated and purified by column chromatography to obtain intermediate B;

[0027] Preparation of intermediate C (R1=R2=R4=H): Under low temperature conditions of -78°C, the prepared intermediate B (1 equiv.) was dissolved in tetrahydrofuran, then n-butyl lithium (3 equiv.) was slowly added and stirred for 1 hour, and then phenylphosphine dichloride (2 equiv.) was added and stirred for 30 minutes. The mixture was returned to room temperature and stirred overnight. After 12 hours, water was added to quench the reaction, and the mixture was extracted and washed with dichloromethane and saturated brine. The organic phase was recovered and dried over anhydrous magnesium sulfate, and the solvent was removed by distillation under reduced pressure. The crude product was then separated and purified by column chromatography to obtain intermediate C;

[0028] Preparation of intermediate D (R1=R2=R3=R4=H): Dimethyl 2-iododiphthalate (R3=H) (1 equiv.), intermediate C (R1=R2=R4=H) (1.2 equiv.), active copper powder (0.2 equiv.), copper iodide (0.05 equiv.), potassium carbonate (1.5 equiv.) and 30 mL 1,2-dichlorobenzene (o-DCB) were stirred and refluxed for 24 hours under an argon atmosphere. After cooling to room temperature, 100 ml of dichloromethane was added and stirred for 10 minutes. Then filtered with a glass filter funnel. The filtrate was concentrated under reduced pressure. The product was purified by silica gel column chromatography using ethyl acetate / petroleum ether (1:9) as the eluent to obtain a light yellow solid product. The yellow solid product and sodium hydroxide (4 equiv.) were then added to an ethanol / water solution (1 / 1, 100 mL). After stirring, the reaction was allowed to react for 12 hours. After cooling to room temperature, the product was acidified with concentrated hydrochloric acid to precipitate a yellow solid, which was filtered with a glass filter funnel, washed with deionized water and dried in a vacuum oven overnight to obtain intermediate D.

[0029] Preparation of intermediate E (R1=R2=R3=R4=H): To a mixture of intermediate D (1 equiv.) in dry dichloromethane (100 mL) was added N,N-dimethylformamide (2 drops, 0.006 equiv.). After adding oxalyl chloride (2.2 equiv.), the mixture was refluxed for 30 minutes. Then, titanium tetrachloride (2 mol / L dichloromethane solution, 2.2 equiv.) was added and refluxed for 3 hours. After cooling to room temperature, the mixture was added dropwise to a 1 mol / L sodium hydroxide aqueous solution and extracted three times with dichloromethane. The organic phase was dried over anhydrous magnesium sulfate. After filtering and evaporating the solvent, the resulting residue was purified by silica gel column chromatography (dichloromethane / petroleum ether (3:1) as eluent) to give an orange-yellow solid product (intermediate E).

[0030] Preparation of compound 1 (R1=R2=R3=R4=H): The prepared intermediate C (1 equiv.) was dissolved in toluene, and 30% hydrogen peroxide (5 equiv.) was added respectively, and the reaction was carried out at room temperature for 12 hours (or sulfur powder or selenphenol was heated to react for 12 hours) to obtain a phosphine-containing intermediate, and trifluoroacetic acid (3 mL) was added respectively and reacted for 5 hours, followed by extraction and washing with dichloromethane and saturated brine, the organic phase was recovered and dried over anhydrous magnesium sulfate, the solvent was removed by distillation under reduced pressure, and then the crude product was separated and purified by column chromatography to produce compound 1.

[0031]

[0032] Those skilled in the art should know that the above-mentioned preparation method is only an illustrative example, and those skilled in the art can obtain other compound structures of the present invention by improving it. It should be understood that the various embodiments described here are only examples and are not intended to limit the scope of the present invention. Therefore, as will be apparent to those skilled in the art, the claimed invention may include variations of the specific embodiments and preferred embodiments described herein. Many of the materials and structures described herein can be replaced with other materials and structures without departing from the spirit of the present invention. It should be understood that the various theories about why the present invention works are not intended to be restrictive. The light-emitting layer of the organic electroluminescent device of the present invention and the organic electroluminescent device are described below.

[0033] The compounds of the present invention can be used as doping materials for the light-emitting layer. The thermal properties and singlet-triplet energy level difference of the compounds of the present invention (the example compounds are compounds 1 to 30) and the existing material TADF1 were measured respectively. The test results are shown in Table 1.

[0034] Table 1: Material properties

[0035]

[0036]

[0037]

[0038] Note: Thermogravimetric temperature Td is the temperature at which the weight loss is 1% in a nitrogen atmosphere, and is measured on a TGA-50H thermogravimetric analyzer from Shimadzu Corporation, Japan, with a nitrogen flow rate of 20 mL / min; PL is the fluorescence emission wavelength of the sample solution, measured using a Japanese Topcon SR-3 spectroradiometer.

[0039] Cyclic voltammetric stability is determined by observing the redox characteristics of the material using cyclic voltammetry.

[0040] Test conditions: The test sample was dissolved in a mixed solvent of dichloromethane and acetonitrile with a volume ratio of 2:1, with a concentration of 1 mg / mL. The electrolyte was an organic solution of 0.1 M tetrabutylammonium tetrafluoroborate or tetrabutylammonium hexafluorophosphate. The reference electrode was an Ag / Ag+ electrode, the counter electrode was a titanium plate, the working electrode was an ITO electrode, and the number of cycles was 20.

[0041] It can be seen from the data in the above table that the compounds of the present invention have a higher pyrolysis temperature and better thermal stability, which provides the possibility for application in devices; at the same time, the smaller singlet-triplet energy level difference improves the efficiency and life of OLED devices using the compounds of the present invention as doping materials.

[0042] Controlled trials:

[0043] Example: Compound 1-30

[0044] The structure of the organic electroluminescent device of the present invention comprises, from bottom to top, a base layer, an anode layer, a hole injection layer, a hole transport layer, a light emitting layer, an electron transport layer / hole blocking layer, an electron injection layer, and a cathode electrode layer.

[0045] The base layer can use the substrate in the conventional organic light-emitting organic electroluminescent device, such as glass or plastic. The anode layer material can use transparent high-conductivity materials, such as indium tin oxide (ITO), indium zinc oxide (IZO), tin dioxide (SnO2), zinc oxide (ZnO), etc. In the production of the organic electroluminescent device in the embodiment of the present invention, a glass substrate is selected and ITO is used as the anode material.

[0046] The hole transport region can be a single-layer structure formed by a single material, a single-layer structure formed by multiple different materials, or a multi-layer structure formed by multiple different materials, among which NPB is a commonly used hole transport material. The hole transport material selected in the preparation of the organic electroluminescent device in the embodiment of the present invention is NPB.

[0047] The structure of the organic electroluminescent device can be a single light-emitting layer or a multi-light-emitting layer structure.

[0048] The structure of a single light-emitting layer is adopted. The light-emitting layer of the organic electroluminescent device of the present invention comprises a main material and a doping material.

[0049] The main material can be composed of a single material or a mixture of multiple materials with different structures; the doping material is an organic compound with acridone as the core in the embodiment of the present invention, and the difference between its singlet and triplet energy levels is not more than 0.2eV, and the singlet and triplet energy levels of the main material are higher than those of the doping material; among them, it is preferred that the difference between the singlet and triplet energy levels of the main material film phase with the lowest luminous energy is not more than 0.15eV; among them, it is preferred that the main material of the luminescent layer is composed of a single material, and the mass doping concentration of the doping material is 3% to 30%, preferably 6%.

[0050] The electron transport region includes one or more of a hole blocking layer, an electron transport layer and an electron injection layer; for example, the electron transport region can have a structure of an electron transport layer / electron injection layer, a structure of a hole blocking layer / electron transport layer / electron injection layer, but is not limited thereto; the electron transport layer uses Alq3 or TAZ or TPBi or a combination of any two of these three materials.

[0051] In the manufacture of the organic electroluminescent device in the embodiment of the present invention, the cathode material selected is LiF / Al.

[0052] The specific structures of several materials used in the present invention are shown below:

[0053]

[0054] The specific preparation process of device 1-30 is as follows:

[0055] The ITO anode layer on the transparent glass substrate layer was cleaned by ultrasonic cleaning with deionized water, acetone, and ethanol for 15 minutes each, and then treated in a plasma cleaner for 2 minutes;

[0056] On the ITO anode layer, HAT-CN was evaporated with a thickness of 10 nm, which served as a hole injection layer. Then, NPB was evaporated with a thickness of 50 nm, which served as a hole transport layer.

[0057] Next, a 40 nm light-emitting layer was evaporated: wherein mCBP was used as the main material, compounds 1-29 were used as doping materials, and the doping mass concentration was 6%, and elements 1-30 were made respectively;

[0058] On top of the light-emitting layer, TPBi is vacuum-deposited with a thickness of 35 nm. This layer of organic material serves as a hole blocking / electron transport layer. On top of the hole blocking / electron transport layer, an electron injection layer LiF is vacuum-deposited with a thickness of 1 nm. This layer is the electron injection layer. On top of the electron injection layer, cathode Al (80 nm) is vacuum-deposited. This layer is the cathode electrode layer.

[0059] Comparative Example 1

[0060] Preparation of organic light emitting element 31: The difference between the organic light emitting element 1-30 prepared in Example 1-30 is that:

[0061] In the light-emitting layer of the organic light-emitting element 31, DSA-ph is used as the doping material, and the doping mass concentration is 6%, and the rest is the same.

[0062] The structure of the organic light emitting element 31 prepared in Comparative Example 1 is:

[0063] ITO / HAT-CN / NPB / mCBP:DSA-ph / TPBi / LiF / Al.

[0064] Comparative Example 2

[0065] Preparation of organic light-emitting element 32: The difference between the organic light-emitting element 1-30 prepared in Example 1-30 is that TADF-1 is used as the doping material in the light-emitting layer of the organic light-emitting element 32, and the doping mass concentration is 6%, and the rest is the same.

[0066] The structure of the organic light emitting element 32 prepared in Comparative Example 2 is:

[0067] ITO / HAT-CN / NPB / mCBP:TADF-1 / TPBi / LiF / Al.

[0068] The device structures of the compounds of the embodiments of the present invention and the comparative examples are shown in Table 2 below:

[0069] Table 2: Device structure table

[0070]

[0071] Performance Testing

[0072] The organic light-emitting elements 1-30 prepared in Examples 1-30 of the present invention and the elements 31 and 32 prepared in Comparative Examples 1 and 2 were subjected to the following performance tests. The performance test results are shown in Table 3.

[0073] Table 3: Performance test results

[0074]

[0075]

[0076] It can be seen from the performance data in Table 3 that the compounds provided in the embodiments of the present invention can make full use of triplet energy compared to traditional fluorescent materials, thereby greatly improving device efficiency. Compared with known TADF materials, the spectral half-width is significantly reduced, and its color purity is significantly improved; the device efficiency roll-off phenomenon is significantly suppressed, and the device life is significantly improved. The specific implementation scheme described above further describes the purpose, technical scheme and beneficial effects of the present invention in detail. It should be understood that the above is only a specific implementation scheme of the present invention, and is not intended to limit the scope of the present invention. Any equivalent changes and modifications made by any technician in the field without departing from the concept and principle of the present invention should belong to the scope of protection of the present invention.

Claims

1. An organic light-emitting material containing a phosphine radical, characterized in that: A compound having a structure shown in Formula 1: wherein R1, R2, R3 and R4 are independently hydrogen, deuterium, halogen, substituted or unsubstituted alkyl having 1 to 20 carbon atoms, substituted or unsubstituted cycloalkyl having 3 to 20 ring atoms, substituted or unsubstituted heteroalkyl having 1 to 20 carbon atoms, substituted or unsubstituted heterocyclyl having 3 to 20 ring atoms, substituted or unsubstituted aralkyl having 7 to 30 carbon atoms, substituted or unsubstituted alkoxy having 1 to 20 carbon atoms, substituted or unsubstituted aryloxy having 6 to 30 carbon atoms, substituted or unsubstituted alkenyl having 2 to 20 carbon atoms , substituted or unsubstituted aryl having 6-30 carbon atoms, substituted or unsubstituted heteroaryl having 3-30 carbon atoms, substituted or unsubstituted silyl having 3-20 carbon atoms, substituted or unsubstituted arylsilyl having 6-20 carbon atoms, substituted or unsubstituted alkylgermanyl having 3-20 carbon atoms, substituted or unsubstituted arylgermanyl having 6-20 carbon atoms, substituted or unsubstituted amino having 0-30 carbon atoms, acyl, carbonyl, carboxylic acid, ester, cyano, isocyano, hydroxyl, thiol, sulfinyl, sulfonyl, phosphino, and combinations thereof.

2. The organic light-emitting material containing phosphine oxygen group according to claim 1, characterized in that: The structure of the compound is as follows:

3. Application of an organic light-emitting material containing a phosphine radical in an organic electroluminescent device, characterized in that: The organic electroluminescent device comprises the light-emitting material according to any one of claims 1 and 2.

4. The use of an organic light-emitting material containing a phosphine oxygen group in an organic electroluminescent device according to claim 3, characterized in that: The luminescent material is doped into the luminescent layer of the organic electroluminescent device.